Construcción de matriz de contabilidad social de Bogotá con énfasis en el sector construcción 2019 (2020)
The main purpose of this paper is to build a Social Accounting Matrix with disaggregated information from the Construction Sector in the city of Bogotá, Colombia for the year 2019. The results obtained through a SAM-based multiplier analysis enabled to quantify how investment on the subsectors of construction impact the economy. Specifically, an investment in the construction subsectors, non-social housing, social housing and nonresidential buildings, have an impact of {dollar}6,45, {dollar}5,91 y {dollar}5,90 Colombian pesos for every one Colombian peso invested. Likewise, the productive sectors were classified by the calculation of the diffusion and absorption effects, which allowed the following conclusion: the three construction subsectors have backward linkages and therefore can be classified as driving sectors of the economy.